Effect of low vs. High carbohydrate diet after glycogen depleting session on 1500m run performance in high-level runners - Venckunas, T.; Minderis, P.; Silinskas, V.; Buliuolis, A.; Maughan, R. J.; Kamandulis, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Carbohydrate (CHO) metabolism is crucial for performance in middle distance races. However, it has so far not been studied robustly if low glycogen stores could interfere with the exercise capacity in the field conditions of relatively short endurance events. It thus remains to be determined if diminished glycogen stores affect sports performance where relatively small amounts of CHO are required to complete the race. The present study tested how 1500 m race is affected by dietary manipulation intended to alter pre-race glycogen reserves in high-level runners. METHODS: National level middle distance runners [n=11 (4 females); age: 21.4 (SD 4.3) y, height: 179.5 (10.5) cm, BMI: 21.2 (1.5), training volume: 12.3 (1.8) h/wk, 69 (25) km/wk] completed, in a randomized cross-over design, a 1500 m time trial (TT) after abundant (High) or restricted (Low) CHO consumption for 2 days after glycogen depleting session (60 min of continuous moderate intensity run followed by 10 x 200 m at planned 1500 m TT pace). CHO intake during 5 days before the each glycogen depleting session averaged 4.8 (1.4) g/kg/d. To keep the diet between glycogen depleting session and TT eucaloric, the Low condition required substitution of most of the diet CHO with fats, while the High condition required consumption of foods high in CHO and low in fats (protein intake was aimed to be unchanged). During Low and High conditions, CHO intake was 5 g/kg/d (average 9.7 (2.6) g/kg/d), respectively. The TT took place in an indoor 200 m track and was run individually with time recorded every 100 m split. Striding pattern, heart rate (HR), capillary blood lactate and glucose dynamics and plasma malondialdehyde (MDA, an oxidative stress marker) response were determined. RESULTS: Time to complete 1500 m TT was slower in Low vs. High condition by 4.5 (4.5) s (i.e. by ~2%; p